2021
DOI: 10.1016/j.phrs.2021.105629
|View full text |Cite
|
Sign up to set email alerts
|

The ameliorative effect of terpinen-4-ol on ER stress-induced vascular calcification depends on SIRT1-mediated regulation of PERK acetylation

Abstract: BackgroundEndoplasmic reticulum (ER) stress-mediated phenotypic switching of vascular smooth muscle cells (VSMCs) is key to vascular calci cation (VC) in patients with chronic kidney disease (CKD). Terpinen-4-ol exerts protective effect against cardiovascular disease, but its role and speci c mechanism in VC remain unclear. We explored whether terpinen-4-ol alleviates ER stress-mediated VC through sirtuin 1 (sirt1) and elucidated its mechanism to provide evidence for its application in the clinical prevention … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 75 publications
(72 reference statements)
2
14
0
Order By: Relevance
“…It was recently shown that Sirt1 inhibition induces hyperacetylation and phosphorylation of eIF2α and PERK to regulate PERK-ATF4 signaling of ER stress ( Prola et al, 2017 ; Kang et al, 2018 ). Additionally, SIRT1 deacetylates PERK physically through physical interactions ( Zhang et al, 2021 ). It has been shown that SIRT1 deacetylates XBP1s and inhibits the transcriptional activity of XBP1s to regulate UPR signaling ( Wang et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…It was recently shown that Sirt1 inhibition induces hyperacetylation and phosphorylation of eIF2α and PERK to regulate PERK-ATF4 signaling of ER stress ( Prola et al, 2017 ; Kang et al, 2018 ). Additionally, SIRT1 deacetylates PERK physically through physical interactions ( Zhang et al, 2021 ). It has been shown that SIRT1 deacetylates XBP1s and inhibits the transcriptional activity of XBP1s to regulate UPR signaling ( Wang et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the fact that its structural features have been largely characterized, knowledge with respect to its functions was limited to proton pumping, and not much is known regarding its function in VSMCs [ 55 , 56 ]. Recently, several studies have reported that ABCC6 might be associated with endoplasmic reticulum stress (ERS) [ 27 , 28 ], and ERS was considered a key mediator for VSMC transdifferentiation towards the synthetic state [ 57 , 58 , 59 ]. Interestingly, previous studies have revealed that RNF213 suppression affects ERS, suggesting an intrinsic connection between RNF213 and ERS [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…25 Among the ERS pathways, the ATF4 pathway is most closely related to the development of VC. 26 ATF4, namely cAMP responseelement binding protein 2 (CREB2), is a common basic/leucine zipper domain transcription factor, which is also in the 5' regulatory region of the human FGF21 gene. 12 When ERS was initiated, ATF4 was activated by one of ERS transducer molecules, PERK, and it can directly up-regulate its downstream molecule, CHOP, to induce osteoblast apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas, the initiation of ERS‐mediated apoptotic process may trigger by multiple signaling pathways 25 . Among the ERS pathways, the ATF4 pathway is most closely related to the development of VC 26 . ATF4, namely cAMP response‐element binding protein 2 (CREB2), is a common basic/leucine zipper domain transcription factor, which is also in the 5' regulatory region of the human FGF21 gene 12 .…”
Section: Discussionmentioning
confidence: 99%